Awal Munculnya Gerakan Inteliktualisme Islam di Indonesia Abad 20 - Wahyuddin G (Jurnal Adabiyah: Humanities and Islamic Studies, 2010)
In the early 20th century, intelectual movement of Islamic reformers comes to bring some changes. This movement was from Moddle East, then spread to all over the world.  The main theme of this movement is to purify Islamic teaching from bid’ah, khurafat, etc. Considering the coming of modern atmosphere, Islamic reformers and institution began to consolidate and accomodate this penetration. Thus, through traditional institution, Islamic traditional thinkers tried to strengthen the main pillars of Islam.